Evaluación del desempeño docente en el área de comunicación de la institución educativa Nº 60080 del distrito de Ramón Castilla 2024 - Nuñez Salate, Maria Isabel (2025)
The purpose of the study was to determine the level of teaching performance in the area of Communication of Educational Institution No. 60080, located in the district of Ramón Castilla, during the 2024 school year. The research adopted a quantitative approach with a descriptive scope. The sample was made up of 876 secondary education students, to whom a questionnaire validated by three experts in the field was applied. The results allowed us to conclude that 63% of the teachers in the Communication area present a medium level of performance, while 30.3% reach a high level and 6.7% show low performance. These findings suggest strengthening pedagogical planning, teaching and teacher participation in school management, in order to optimize educational quality.